2009
DOI: 10.1007/s10295-009-0571-6
|View full text |Cite
|
Sign up to set email alerts
|

Early succession of bacterial biofilms in paper machines

Abstract: Formation of biofilms causes severe problems in paper machines, and hence financial costs. It would be preferable to prevent attachment of the primary-colonizing bacteria than to control the growth of secondary communities, which are sheltered by exopolysaccharide slime layers. We have therefore investigated the early succession of paper-machine biofilms by incubating stainless-steel test coupons in the process water-flow lines in two paper machines operating in slightly alkaline conditions in temperatures (45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…Most information on microorganisms in paper mills is based on traditional bacterial isolation and characterization [23,27,31,33,34,41,44], which suffers from well-known bias associated with all cultivation-based approaches. Only a few studies using modern molecular methods are found that describe the diversity of bacteria potentially involved in biofouling in the actual papermaking process and they have focused on biofilms of paper machines using wood pulp [24] or wood pulp with a small fraction of recycled fibers [42] processed under thermophilic conditions. There are also a couple of studies on bacterial communities in the wastewater treatment process in paper mills [12,16].…”
Section: Introductionmentioning
confidence: 99%
“…Most information on microorganisms in paper mills is based on traditional bacterial isolation and characterization [23,27,31,33,34,41,44], which suffers from well-known bias associated with all cultivation-based approaches. Only a few studies using modern molecular methods are found that describe the diversity of bacteria potentially involved in biofouling in the actual papermaking process and they have focused on biofilms of paper machines using wood pulp [24] or wood pulp with a small fraction of recycled fibers [42] processed under thermophilic conditions. There are also a couple of studies on bacterial communities in the wastewater treatment process in paper mills [12,16].…”
Section: Introductionmentioning
confidence: 99%
“…Scientific literature on the analysis of bacterial communities within the different compartments of a paper mill is nowadays scanty, especially when considering cultureindependent approaches (Tiirola et al 2009, Lahtinen et al 2006, Granhall et al 2010, Rasimus et al 2011). The majority of available studies have adopted culture-dependent techniques (Desjardins and Beaulieu 2003, Kolari 2003, Kolari et al 2003, Suihko et al 2004, Suihko and Skyttä 2009, thus underestimating the microbial diversity of the original sample.…”
Section: Discussionmentioning
confidence: 99%
“…Cloacibacterium showed roughly comparable abundance percentages in both library (24.8%) and isolates (36.8%). Strains of the species Cloacibacterium normanense were previously isolated from biofilms of paper mill machines using both culture-dependent (Suihko and Skyttä 2009) and culture-independent (Tiirola et al 2009) approaches. Bacteria belonging to this genus are characterized by a facultative anaerobic metabolism and they produce colored pigments ranging from yellow to orange.…”
Section: Snapshot Analysis Of White Watermentioning
confidence: 99%
“…A pentachlorophenol degrading bacterium Flavobacterium (Gonzalez and Hu 1991; Suihko and Shooter 2009) and Tepidimonas (Tiirola et al 2009) have been reported in the process of paper production. P. putida and Enterobacter sp.…”
Section: Sequencing Of Dgge Bands and Phylogenetic Analysismentioning
confidence: 99%